Clinical, MRI and electrographic characteristics of three children with Hemiconvulsion-Hemiplegia/Hemiconvulsion-Hemiplegia-Epilepsy (HH/HHE) syndrome–A rare childhood epileptic encephalopathy - Singh Sudan, Yeeshu; Vinayan, K. P.; Roy, Arun Grace (International Journal of Epilepsy, 2017)
Hemi convulsion-Hemiplegia-Epilepsy (HH/HHE) syndrome is a very rare catastrophic epileptic syndrome in childhood which follows a prolonged focal motor status epilepticus in infancy and early childhood. Here we are describing the clinical, MRI and electrographic characteristics along with long term outcome of three children with HH/HHE syndrome. A review of the current literature on HH/HHE syndrome is attempted stressing on the diagnostic features and the neurobiological relationship between prolonged focal motor status epilepticus and subsequent development of HH/HHE syndrome. Early identification of this syndrome may help the treating physician in providing families with a relatively accurate prognosis regarding the functional outcome and subsequent development of epilepsy.
Keywords: Hemiconvulsion; Hemiplegia; Epilepsy; Status epilepticus